History of Local Newspapers in Chiangmai and Lampang - photchanalawan, phinyaphan (King Prajadhipok’s Institute Journal, 2020)
This article aims to explore the adaptation of local newspapers in the context of socio-economy and politics. Local newspapers are local organizations that have passed the experience with the local society for a long time, and they also relate to the literacy rate of the local people. So, this study focuses on the sender and the reader in the city in the first place. The adaptation of local history reflects the fluidity of information in many ways. This study also explores the connection between the mass media and local politics. The survival of some local media outlets seems not to show respect for to the professional ethics of the mass media as the professional firm. The rapid changes in society, news, and information challenge local newspapers. News can be accessed from central media sources in Bangkok, and new media technology draws readers away from newspapers in favor of computers or mobile phone screens. Some media have adapted but some have not. Moreover, some media outlet owners decide to retire and close their media outlets.